2008
DOI: 10.4141/cjps07026
|View full text |Cite
|
Sign up to set email alerts
|

Time of nitrogen application affects nitrogen use efficiency of wheat in the humid pampas of Argentina

Abstract: . 2008. Time of nitrogen application affects nitrogen use efficiency of wheat in the humid pampas of Argentina. Can. J. Plant Sci. 88: 849Á857. Nitrogen (N) fertilization is an important management practice to increased grain yield; however, it is imperative to increase nitrogen use efficiency (NUE) in order to diminish risks of environmental pollution. The objective of this study was to determine the effect of fertilization times on wheat grain yield, grain N accumulation and grain N recovery efficiency (RE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
2
19
2
1
Order By: Relevance
“…Peralta et al, 2014, found that NUE in similar field with barley crop varied between 1.3 and 18 kg of grain per kg N applied, which decreased as the applied N rate increased. Barbieri et al (2008) and Velasco et al (2012), found values similar to the present study, although they did not identify MZ. These authors mentioned that the low average values of NUE may be attributed to water stress during the growing season since in years without water stress, values of NUE were greater (see Fig.…”
Section: Management Zones and Nitrogen Ratesupporting
confidence: 87%
See 1 more Smart Citation
“…Peralta et al, 2014, found that NUE in similar field with barley crop varied between 1.3 and 18 kg of grain per kg N applied, which decreased as the applied N rate increased. Barbieri et al (2008) and Velasco et al (2012), found values similar to the present study, although they did not identify MZ. These authors mentioned that the low average values of NUE may be attributed to water stress during the growing season since in years without water stress, values of NUE were greater (see Fig.…”
Section: Management Zones and Nitrogen Ratesupporting
confidence: 87%
“…In fields with spatially variable N needs, this practice leads to frequent mismatches between N fertilizer rate and crop N need. Over-application of N increases the probability of NO 3 -N leaching below the root zone (Aparicio et al, 2008;Barbieri et al, 2008) while underfertilization limits yields and may restrict economic returns (Scharf and Lory, 2002). Efficient N fertilizer management is critical for profitable crop production and long-term soil and environmental quality.…”
Section: Introductionmentioning
confidence: 99%
“…A similar behavior for that relationship was observed when NO 3 − -N content was determined at 0-40 cm deep (Figure 3). Lower yield related to N application at planting might be explained primarily by the occurrence of greater N loss by leaching and, to a lesser extent, by denitrification (Picone, Videla, and García 1997;Barbieri, Sainz Rozas, and Echeverría 2008). Greater NUE for N applications at tillering compared to planting have been also reported by other authors (Melaj et al 2003;Videla et al 2004;López Bellido, López Bellido, and López Bellido 2006;Barbieri, Sainz Rozas, and Echeverría 2008).…”
Section: Grain Yieldmentioning
confidence: 73%
“…The greater proportion of soils are Typic Argiudolls, with loam texture at the surface layer, loam to clay loam at subsurface layers, and sandy loam below 110 cm deep, and Petrocalcic Paleudoll, which presents discontinuous layers of petrocalcic horizon below 0.8 m and greater clay contents at subsurface layers than Typic Argiudolls. More details of weather and soils in that area were described in Barbieri, Sainz Rozas, and Echeverría (2008).…”
Section: Introductionmentioning
confidence: 99%
“…When applying the nutrients this way, the synchrony between nitrogen availability and crop nitrogen demand , Shanahan et al 2008, Hancock et al 2011 can be enhanced and the threat of water soluble nutrients leaching to water systems can be decreased , Barberi et al 2008, Singh et al 2008, Basso et al 2011, Walsh et al 2013). Many studies have used split applications with predefined application rates (Esala 1991, Peltonen 1995, Olesen et al 2000, Asseng et al 2001, Kuisma 2002, Singh et al 2008, Basso et al 2009, Basso et al 2011, Hancock et al 2011) but observing the current growth conditions in defining the second application rate has also been suggested (Asseng et al 2001, Hakojärvi and Hautala 2010, Basso et al 2011, Walsh et al 2013.…”
Section: Introductionmentioning
confidence: 99%